Fast track consultation in the infectious diseases department of a French university hospital: evaluation of the service delivered to the general practitioner. Issue 2 (1st February 2018) - Weiss, Nicolas; Courjon, Johan; Pradier, Christian; Caisso, Cécile; Mondain, Véronique; Roger, Pierre-Marie; Demonchy, Elisa
Abstract: Purpose: Since 2010, the Infectious Diseases (ID) department of the Nice university hospital (France) has implemented a fast track consultation (FTC): it allows General Practitioners (GP) to directly reach an ID specialist through a dedicated phone number for initial advice. Depending on the first observation, a formal consultation can be planned within 48 h. Our aim was to evaluate in a pilot study, the contribution of the FTC regarding the management of patients 28 days after the first phone contact. Methods: This prospective current care study was conducted between November 2014 and January 2015 in our ID department. The GP indicates the most likely diagnosis, the therapeutic strategy and the patient's management he would have applied. After the formal consultation, ID specialist provides his diagnosis, therapeutic strategy and patient's management. An adjudicative committee has evaluated the benefit of the FTC after 28 days of follow-up. Results: Fifty-one patients referred by 49 GP were included. ID specialists modified the diagnosis in 22 (43%) patients, antibiotic treatment in 35 (68%) and treatment plan in 30 patients (59%). FTC provided at least one service for 41/51 patients (94%): antibiotic treatment was reassessed for 11 (22%) patients, averted for 9 (18%) patients, unnecessary hospitalization was avoided for 8 (16%) of them and emergency room visit averted for 5 (10%) patients. Conclusions: FTC can provide significant improvement in the management of the patients in terms of decrease in unnecessary hospitalization, emergency room visit averted and appropriate use of antibiotics.